Carotid Intima-Media Thickness in Patients with Non-Alcoholic Fatty Liver Disease - Aashfa Hassan Shaikh; Sabeen Aatif; Tanweer Ahmed (Journal of Basic & Applied Sciences, 2013)
Objective: To measure the thickness of Carotid Intima Media (CIMT) in patients with Non-Alcoholic Fatty Liver Disease (NAFLD) and compare it with Controls, to establish the strong association of NAFLD with increased CIMT. Method/Setting: Fifty four patients with sonographically proven NAFLD and 50 controls were examined for CIMT. Carotid scanning was performed on Aloka 3500 Doppler Unit. Results: The mean Intima Media Thickness in NAFLD group was 0.80±0.12 and in controls 0.58±0.15 (p= <0.0001). Carotid plaque was found in 24.07% patients in NAFLD group. Conclusion: NAFLD as an independent risk factor for atherosclerosis and cardiovascular disease. Measurement of CIMT is a reliable, non-invasive tool for early detection of atherosclerosis in these patients.